Profesionalisme Guru Madrasah Ibtidaiyah Melalui Kelompok Kerja Guru (KKG) di Kecamatan Gantarang Kabupaten Bulukumba - Nur Rahmi (El-Idare, 2019)
This article discusses the teachers’ professionalism of Madrasah Ibtidaiyah through the Teachers Working Group at Gantarang District of Bulukumba Regency. The approach used is qualitative which is reviewed based on the phenomenological. Informan in this article is a supervisor, head of Madrasah and teachers of Ibtidaiyah Madrasah who are involved in the activities of KKG. The data collection techniques used are observations and interviews. Processing techniques and data analysis through data reduction, data presentation, and verification or withdrawal of conclusions. KKG Madrasah Ibtidaiyah in Gantarang District has been conducted and is very helpful teachers in developing and improving their competence as well as a place to share teaching experience. Through the activities of the KKG, teachers are given learning guidance and given opportunities to share experiences, teaching techniques, and scientific references so as to make it easier for teachers to perform the learning tasks in the Madrasah.